Impact of a specialized care program in the prevention and managing of skin integrity disorder in pediatric patients after open heart surgery - Faramarz Kalhor; Mayam Mlekpour; Ahmadreza Yazdannik; Hamid Bigdelian (BMC Pediatrics)
Abstract Background Patients undergoing cardiac surgery, particularly children, are at an increased risk of experiencing skin integrity disorders and pressure ulcers, attributed to the underlying disease and prolonged surgical durations. This study aims to examine the impact of a specialized care program on the incidence and advancement of skin integrity disorders in children aged 1 month to 6 years after open heart surgery. Materials and methods This quasi-experimental study, registered with the Iranian Registry of Clinical Trials (IRCT) under the identifier IRCT202008250458515N12 on November 11, 2020, involved 80 children admitted to the critical care unit of a teaching hospital. The participants were divided into two groups: an intervention group and a control group, each consisting of 40 children. The intervention group received targeted care program measures, while the control group followed standard care procedures. The risk of pressure ulcer development, incidence of skin damage, and pressure ulcer status were assessed and recorded using the Braden Q Scale and the Pressure Ulcer Scale for Healing (PUSH) both before the intervention and seven days after hospitalization. Findings The incidence of skin damage in the intervention group (45%) was significantly lower than that in the control group (62.5%) (P < 0.001). Additionally, the average scores for PUSH and Braden Q in the intervention group were 2.95 ± 0.67 and 27.48 ± 1.50, respectively, whereas in the control group, they were 5.70 ± 1.07 and 25.05 ± 2.22, respectively. These differences were statistically significant (P < 0.001). Conclusion According to the results, the designed focused care program can lead to the reduction of the risk of skin damage and the improvement in pressure ulcers; thus, it is recommended to be considered in the special care units.